1995
DOI: 10.1089/aid.1995.11.273
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of SIV in Lymph Nodes of Serially Sacrificed Rhesus Monkeys

Abstract: Rhesus monkeys were inoculated with SIVDeltaB670 and sacrificed 2, 4, 8, and 24 weeks after inoculation or when moribund. Two monkeys predicted to have a rapid disease course and two predicted to have a slower disease course were sacrificed at each time point. Lymph nodes were studied by histopathology, immunohistochemistry, in situ hybridization, electron microscopy, flow cytometry for lymphocyte subsets, and mitogen responsiveness. A greater selective decrease in peripheral CD4+CD29+ (helper-inducer/memory) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…This analysis was done because it was previously reported that lymphoid organs are a major source of virus in HIV-infected patients and SIVmac-infected macaques (5,23,26). The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis was done because it was previously reported that lymphoid organs are a major source of virus in HIV-infected patients and SIVmac-infected macaques (5,23,26). The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The AID 50 was calculated using software developed by John Spouge (57). The SIV/DeltaB670 stock consists of at least 22 different genotypes characterized by nucleotide sequencing of the hypervariable region V1 of the envelope gene (2) and includes both the macrophage-and lymphocyte-tropic strains (6,7,50). SIV/DeltaB670 induces the full range of SIV-associated disease, including immunosuppression, encephalitis (37,65), and pneumonia (8,36).…”
Section: Methodsmentioning
confidence: 99%
“…Macaques infected by the simian immunodeficiency virus SIVmac experience a broad range of progression rates (rapid, normal, or slow progression) as is the case for human immunodeficiency virus type 1 (HIV-1)-infected individuals (49). Similar to the situation in humans (12,15), continuous viral replication takes place in lymphoid tissues, such as lymph nodes (LNs), throughout the course of SIVmac infection (2,27,39). As also seen in humans (30), a strong correlation exists between the pattern of viral replication and the clinical course of the infection (10,21).…”
mentioning
confidence: 98%